Tartary buckwheat on nitric oxide-induced inflammation in RAW264.7 macrophage cells. Issue 8 (5th August 2015) - Choi, Soo Yeon; Choi, Ji Yeon; Lee, Jeong Min; Lee, Sanghyun; Cho, Eun Ju
<x xml:space="preserve">Abstract</x> We investigated the effects of tartary buckwheat (TB, Fagopyrum tataricum) on the production of pro-inflammatory mediators in lipopolysaccharide (LPS)- and interferon (IFN)-γ-stimulated RAW264.7 cells.